EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI KEMAMPUAN AWAL - Yuliasari, Nova (STKIP YPM Bangko, 2018)
This study aims to describe mathematical problem solving abilities in terms of the initial ability to use cooperative learning models Teams Game Tournament type is better than learning. Quantitative research with experimental methods. The research design is a 2 x 3 factorial design with a population of 8 classes. The sampling technique uses Simple Random Sampling, grouped based on initial abilities. The technique of collecting data through tests in the form of essay questions. Based on the results of testing the data analysis prerequisites, it is known that the data are normally distributed and homogeneous variance, the data analysis techniques used are t-test and two-way anova. From the data analysis it can be concluded that students who are taught with the cooperative TGT model as a whole and students with early abilities are better than conventional learning, while students with high and low initial abilities are no more than conventional learning, and there are interactions between learning models and initial abilities affecting problem solving skill.